Factor structure of the Posttraumatic Growth Inventory in a Spanish sample of adult victims of interpersonal violence in childhood - Pajón, Laura; Greco, Ana Martina; Pereda, Noemí; Gallardo-Pujol, David (Revista de Psicopatología y Psicología Clínica, 2020)
Abstract: Research interest in trauma as a possible cause of growth has increased in recent decades. The Posttraumatic Growth Inventory (PTGI) is widely used to measure growth after traumatic events. The present study aimed at validating the Spanish version of the PTGI in a sample of 243 young adults (age range from 18 to 35 years old, M = 21 years, SD = 2.5) who experienced interpersonal victimization during their childhood and/or adolescence. Preliminary analyses showed acceptable reliability for the PTGI subscales (Cronbach’s α ranging from .61 to .89). Exploratory factor analysis revealed a four-factor structure that included «new perception of life», «relating to others», «personal strength», and «spiritual change». All types of victimization correlated significantly with PTGI scores. These findings provide support for the factorial validity of the PTGI and the use of the PTGI in future research examining posttraumatic growth among Spanish victims of interpersonal violence in childhood. Keywords: Victimization; Posttraumatic Growth Inventory; trauma; growth. Estructura factorial del Inventario de Crecimiento Post-traumático en una muestra española de víctimas adultas de violencia interpersonal durante la infancia Resumen: El interés científico en el trauma como posible fuente de crecimiento ha aumentado en las últimas décadas, siendo el Inventario de Crecimiento Post-traumático (PTGI) uno de los instrumentos más usados para medirlo. El estudio pretende validar la versión en castellano del PTGI en una muestra de 243 adultos jóvenes (entre 18 y 35 años, M = 21 años, DT = 2.5), víctimas de violencia en la infancia y/o adolescencia. Los análisis mostraron una fiabilidad aceptable para todas las subescalas (α =.61- .89). El análisis factorial exploratorio reveló una estructura de cuatro factores: «nueva percepción de la vida», «relación con los demás», «fuerza personal» y «cambio espiritual». Todos los tipos de victimización correlacionaron significativamente con las puntuaciones del PTGI. Los resultados aportan evidencia sobre la validez de la estructura interna del PTGI y el uso del PTGI en futuras investigaciones que examinen el crecimiento post-traumático en víctimas españolas de violencia interpersonal durante la infancia. Palabras clave: Victimización; inventario de crecimiento post-traumático; trauma; crecimiento.